The Effects of Temperature and Humidity on Skin Leishmania in Heat Management This is a master's thesis - Ahmed, Prof.Dr. Soran Muhammad Amin Ahmed; Qadir, Sirwan Mustafa Qadir (Sulaimani Journal for Humanities, 2025)
This study investigates the impact of climatic factors—especially temperature and humidity—on the incidence of Leishmaniasis in the Garmian region. The research is based on meteorological data from weather stations in Kalar and Kifri and disease case records from the Directorate of Health and Preventive Care in Garmian, covering the period 2015–2023. Both descriptive and analytical methods were employed to explore how monthly and yearly climatic variations influence infection rates.Statistical tools used included Pearson’s correlation, simple linear regression, and multiple linear regression. Results showed that temperature had a stronger negative effect on Leishmaniasis cases compared to humidity. The correlation between temperature and disease incidence was –0.74, and the simple regression coefficient was –19.22. This suggests that with every 1°C increase in temperature, about 19.22 fewer cases occurred. In multiple regression analysis, the effect of temperature remained negative at –18.48, confirming the inverse relationship. Conversely, humidity showed a positive correlation (r = 0.73) in simple analysis, with a regression coefficient of 9.22—indicating an increase in cases with higher humidity. However, in the multiple regression model, the humidity coefficient dropped to –2.55, implying that other factors may moderate its impact when combined with temperature.A detailed table summarized the results across Kalar District, Qoratu and Maidan Subdistricts, and Kifri District. The month of June consistently showed the lowest infection rates.Based on these findings, the study concluded with several practical recommendations aimed at improving disease control and prevention strategies in the region.
Keywords: Correlation; Leishmaniasis; Temperature; Humidity; Climate Impact; Garmian Administration